Global warming policy in Japan and Britain : Interactions between institutions and issue characteristics - Oshitani, Shizuka (Book collections on Project MUSE., 2006)
The author explores how different countries responded to the common policy imperative of tackling global warming. He discusses why their responses were similar in some aspects and different in others, taking Japan and Britain as examples.